Rewetting and litter addition influence mineralisation and microbial communities in soils from a semi-arid intermittent stream - McIntyre, Rebecca E.S.; Adams, Mark A.; Ford, Douglas J.; Grierson, Pauline F. (Soil biology & biochemistry, 2009)
Nitrogen (N) and carbon (C) mineralisation are triggered by pulses of water availability in arid and semi-arid systems. Intermittent streams and their associated riparian communities are obvious ‘hot spots’ for biogeochemical processes in arid landscapes where water and often C are limiting. Stream landscapes are characterized by highly heterogeneous soils that may respond variably to rewetting. We used a laboratory incubation to quantify how N and C mineralisation in rewetted soils and sediments from an intermittent stream in the semi-arid Pilbara region of north-west Australia varied with saturation level and substrate addition (as ground Eucalyptus litter). Full (100%) saturation was defined as the maximum gravimetric moisture content (%) achieved in free-draining soils and sediments after rewetting, with 50% saturation defined as half this value. We estimated rates and amounts of N mineralised from changes in inorganic N and microbial respiration as CO 2 efflux throughout the incubation. In soils and sediments subject to 50% saturation, >90% of N mineralised accumulated within the first 7 d of incubation, compared to only 48% when soils were fully saturated (100% saturation). Mineralisation rates and microbial respiration were similar in riparian and floodplain soils, and channel sediments. N mineralisation rates in litter-amended soils and sediments (0.73 mg N kg −1 d −1) were only one-third that of unamended samples (3.04 mg N kg −1 d −1), while cumulative microbial respiration was doubled in litter-amended soils, suggesting N was more rapidly immobilized. Landscape position was less important in controlling microbial activity than soil saturation when water-filled pore space (% WFPS) was greater than 40%. Our results suggest that large pulses of water availability resulting in full soil saturation cause a slower release of mineralisation products, compared to small pulse events that stimulate a rapid cycle of C and N mineralisation–immobilization.